The Routledge Handbook of Collective Intelligence for Democracy and Governance (Taylor & Francis, 2023)
The Routledge Handbook of Collective Intelligence for Democracy and Governance explores the concepts, methodologies, and implications of collective intelligence for democratic governance, in the ﬁrst comprehensive survey of this field.